2021
DOI: 10.3389/fpubh.2021.628178
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning in Teaching Emergency Disaster Response Among Undergraduate Medical Students in Malaysia

Abstract: Introduction: Teaching disaster response medicine (DRM) to medical students requires considerable resources. We evaluate the effectiveness of e-learning in teaching emergency disaster response (ELITE-DR), a novel initiative, in educating medical students of the cognitive aspect of DRM.Methods: A prospective cross-sectional study among pre-clinical year medical students was carried out to determine their knowledge on DRM and perception regarding the ELITE-DR initiative using a validated online questionnaire. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Most of the studies (n = 3) were published in 2020 and 2021. One article reported on an undergraduate nursing programme [ 18 ], while the other three journals reported on an undergraduate medical programme [ 19 ]. Only two studies mentioned using models to underpin their evaluation processes, namely, the SWOT analysis [ 20 ], the Kirk Patrick model [ 33 ] and the force field analysis [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies (n = 3) were published in 2020 and 2021. One article reported on an undergraduate nursing programme [ 18 ], while the other three journals reported on an undergraduate medical programme [ 19 ]. Only two studies mentioned using models to underpin their evaluation processes, namely, the SWOT analysis [ 20 ], the Kirk Patrick model [ 33 ] and the force field analysis [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Raghuveer and Nirgude [22] reported that educators must be proficient and competent in facilitating e-learning. Authors of all included studies evaluated the online teaching and delivery skills of educators [18][19][20][21][22][23]. Moreover, the requirement of educators related to e-learning, including their perception and attitude, was included as part of needs assessments.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…15 There are 67 universities in Malaysia, including both public and private; only a few offer DM training for undergraduates, and none offer any certification. 16,17 As a result, research in this field is limited, as evidenced by the 154 journals linked to DM that were discovered after a 30-year search of five journal databases (from 1991 through 2021). Chih-Hao Lin has published similar findings in regard to Taiwanese researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 outbreak has disrupted the offline face-toface teaching model, and when all students must leave the classroom to prevent gathering and spreading the virus, online learning may be the only solution [as shown in references (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)]. In recent years, many universities have begun to promote online teaching models [as shown in references (33)(34)(35)].…”
Section: Introductionmentioning
confidence: 99%